Influence of differences in current GOSAT XCO2 retrievals on surface flux estimation. Issue 7 (2nd April 2014) - Takagi, Hiroshi; Houweling, Sander; Andres, Robert J.; Belikov, Dmitry; Bril, Andrey; Boesch, Hartmut; Butz, Andre; Guerlet, Sandrine; Hasekamp, Otto; Maksyutov, Shamil; Morino, Isamu; Oda, Tomohiro; et al.
Abstract: We investigated differences in the five currently‐available datasets of column‐integrated CO2 concentrations ( X C O 2 ) retrieved from spectral soundings collected by Greenhouse gases Observing SATellite (GOSAT) and assessed their impact on regional CO2 flux estimates. We did so by estimating the fluxes from each of the five X C O 2 datasets combined with surface‐based CO2 data, using a single inversion system. The five X C O 2 datasets are available in raw and bias‐corrected versions, and we found that the bias corrections diminish the range of the five coincident values by 30% on average. The departures of the five individual inversion results (annual‐mean regional fluxes based on X C O 2 ‐surface combined data) from the surface‐data‐only results were close to one another in some terrestrial regions where spatial coverage by each X C O 2 dataset was similar. The mean of the five annual global land uptakes was 1.7 ± 0.3 GtC yr −1, and they were all smaller than the value estimated from the surface‐based data alone. Key Points: Differences in five recent satellite‐based CO2 datasets were investigated Influence of CO2 data differences on surface CO2 flux estimation was assessed Impact on flux estimates varies with number density of available data